The Haier Group: Improvement Upon Success - Ben-Jacob, Tyler (European Scientific Journal, ESJ, 2016)
This paper discusses the necessary elements for a company to be successful. It considers internal and external components, including aspects of management, marketing, and employee loyalty. An analysis of the strategies used by the Haier Group, a producer solely of refrigerators in 1984, to rise to a company that dominated the market of white goods by 2014 is presented. After delving into the processes and techniques used by this company to grow into a global enterprise, the discussion elaborates with suggestions that could make this remarkably successful company advance even more in today’s market.